Decomposição de camadas do Mulch e contribuição para o carbono e nitrogênio do solo - Schu, Adriane Luiza (2019)
Recent studies have shown that mulches formed by different amounts of cultural residues have similar decomposition rates, evidencing the reduced effect of contact between soil and residue on decomposition. Recent studies have shown that the rate of decomposition of mulches with different amounts of cultural residues is not influenced by the greater contact of the residues with the soil. This result is attributed to the formation of a decomposition gradient in the mulch, conditioned by the moisture of the residues. Thus, these cultural residues may have different decomposition rates depending on the position in the mulch and thus differ as to the contribution to the C and N of the soil. Thus, the objective of this study was to evaluate the contribution of rice crop residues from the rice present in different layers of the mulch to the accumulation of C and N in the soil. For this, a laboratory incubation was conducted under controlled temperature conditions for 112 days. The aerial part of the rice (Oryza sativa L.), previously or not enriched with 13C and 15N, was added to the soil surface contained in 5 cm diameter and 12.5 cm high PVC tubes, forming the following treatments three layers labeled, integral mulch (Mulch); top layer (top layer); middle layer (middle layer); low layer (low layer). In addition, a treatment with soil only was used, without addition of residues (Soil). The soil used in the experiment was a Typic Paleudalf. The evaluation of C mineralization was carried out by measuring the 13CO2 released during the decomposition of the residues. The amount of 13C and 15N remaining in the residues and in the soil was determined on two evaluation dates (28 and 112 days after assembly of the incubation). The major contribution in the addition of 13C in the soil was from residues of the lower layer of the mulch, as well as a smaller amount of 13C remaining was found in the residues of this layer. A higher amount of C accumulated in the soil per unit of mineralized C was found in the lower layer of the mulch, indicating a greater microbial efficiency in the use of the C of the residues of this layer. The dynamics of 15N in the residues and in the soil was not influenced by the position of the residue layer in the mulch. The results of this study show that in the short term the location of the residue layer in the mulch affects its contribution to soil C.